Pemberdayaan Masyarakat melalui Kegiatan Seni di Komunitas Celah-Celah Langit (KCCL) - Mahesa El Gasani (Universitas Padjadjaran, 2019)
This research discusses community empowerment by Komunitas Celah-Celah Langit, Bandung. This research applied qualitative approach in particular auto-ethnography. Results of this research suggest that the empowerment process by Komunitas Celah-Celah Langit has been carried out through in three ways. First, by providing physical facilities such as a performance room, a library, and a discussion room to create people’s awareness of education through art. Second, by providing skill-based facilities, such as theater training in order to enhance people’s art creativity, especially theather. Third, by facilitating non-art self-improvement for people, such as cultural, education, and environmental awareness.